Impact evaluation for policy making: a close look at Latin American countries with weaker research capacities - Alzúa, María Laura (2012)
With the transition to market-based systems, many countries are designing and implementing social policies targeted to specific populations, e.g. social protection to poor people, job training programs to the youth and the unemployed, agricultural development programs to farmers. Decision-makers, donors and taxpayers are interested in knowing whether the programs have the expected benefits, hence demanding rigorous assessments of the impacts of social policies and programs.2 This could further foster accountability in public expenditures and may lead to improvements in program design and implementation, if installed within the right institutional framework (Briceño and Gaarder, 2010) and in combination with other evaluation tools such as process evaluations, monitoring mechanisms, qualitative information, etc.